A serendipitous MeerKAT discovery of a neutral hydrogen (H I) rich galaxy group with megaparsec-scale filamentary-like structure - Lawrie, Graham David (My University, 2024)
Neutral hydrogen (H I) makes up a significant portion of cold gas in galaxies, and is an important component within galaxy formation and star formation. Environmental effects within cosmological overdensities such as galaxy clusters and groups are known to dramatically influence galaxy evolution, and H I content and morphology are important diagnostics thereof. This thesis reports the discovery of an H I galaxy group of 32 galaxies at z ∼ 0.041, as well as detail the H I and multiwavelength properties. The group, being H I-rich and spatially-resolved, allows for a detailed study of the role of the environment in the early stages of transforming its members’ gas content. Star formation rate (SFR) for individual galaxies is derived from near and mid-infrared photometry, and host galaxy study is done using sub-arcsecond imaging with Dark Energy Survey. The group appears to have a Mpc-scale filamentarylike structure. The data used in this project was observed as part of the MeerKAT Galaxy Cluster Legacy Survey (MGCLS), a radio continuum survey, but shows the potential for commensal spectral line and continuum science with modern radio interferometers.
A research report submitted in partial fulfilment of the requirements for the degree Master of Science to the Faculty of Physics, School of Geosciences, University of the Witwatersrand, Johannesburg, 2023
Keywords: Neutral hydrogen; Galaxy clusters; Cold gas